2012
DOI: 10.1016/j.polymer.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced two-stage reactive polymer network forming systems

Abstract: In this study, we develop thiol/acrylate two-stage reactive network forming polymer systems that exhibit two distinct and orthogonal stages of curing. Using a thiol-acrylate system with excess acrylate functional groups, a first stage polymer network is formed via a 1 to 1 stoichiometric thiol-acrylate Michael addition reaction (stage 1). At a later point in time, the excess acrylate functional groups are homopolymerized via a photoinitiated free radical polymerization to form a second stage polymer network (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Samples were tested within 1 h after the first cure. During measurements, the temperature was ramped from room temperature (24)(25) C) to a constant temperature of 28 C over three hours. Each sample was measured under dark conditions using a vertical tension film mode at 15 lm amplitude and 1 Hz frequency oscillation.…”
Section: Temporal Study Of Mechanical Properties After First Curementioning
confidence: 99%
See 2 more Smart Citations
“…Samples were tested within 1 h after the first cure. During measurements, the temperature was ramped from room temperature (24)(25) C) to a constant temperature of 28 C over three hours. Each sample was measured under dark conditions using a vertical tension film mode at 15 lm amplitude and 1 Hz frequency oscillation.…”
Section: Temporal Study Of Mechanical Properties After First Curementioning
confidence: 99%
“…13(a,b)]. After 4 days in water at 85 C the thiol-ene-epoxy samples results in a 10% reduction in storage modulus at 25 C, and in a < 10 C reduction of the T g . The broadening of the tan delta curves [ Fig.…”
Section: Stability and Curing Behavior During The First Curingmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] polymer system, to engineer polymer networks that have a distinct initial set of properties after a polymerization reaction that is self-limiting and a distinct second set of final properties that are achieved oncommand by photoinitiating a second polymerization reaction that does not occur at all during the first reaction and is orthogonal to the initial reaction. [5,6] The general concept of the two-stage reactive polymer system is shown in Figure 1. Previous studies have shown the advantages of a step-wise approach; [7,8] in this study to enable these two stable and distinct reaction stages to occur within the same polymer network, an amine catalyzed thiol-acrylate Michael addition reaction was used to form the initial polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In our previous work, we exploited the ability to incorporate excess acrylate functional groups to enable greater versatility of these systems. [5,6] In this manner, after the initial Michael addition reaction, residual acrylate groups are pervasive throughout the polymer network yet stable in the absence of a radicalgenerating trigger. At a later time, the remaining acrylate functional groups are photopolymerized to form highly crosslinked polymer networks with mechanical performance much different from the initial polymer network.…”
Section: Introductionmentioning
confidence: 99%